Perancangan Temperatur Badan Mandiri Yang Terhubung Dengan Pintu Dan Wastafel Otomatis Dengan Arduino - Heru Rudianto; Daniel Rudiaman Sijabat (Prosiding SISFOTEK, 2021)
In early 2020, the world was shocked by an outbreak of a new pneumonia that started in Wuhan, Hubei Prov-ince, which then spread rapidly to more than 190 countries and regions. This outbreak is named coronavirus disease 2019 (COVID-19) caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). The spread of this disease has had a wide social and economic impact. Meanwhile, in an effort to break the chain of the virus, by avoiding people who are sick with fever and in direct contact with humans, therefore ideas and ideas were created to try to build a body temperature detection device for minimarkets or public places that do not have officers to check. body temperature of incoming visitors. It also reduces physical contact between hu-mans, which will later be connected to the automatic door and water sink. The purpose of building this tool is to support and participate in stopping the spread of the virus so that it does not spread and ends soon.